Current opinion: Is added dietary sugar detrimental to health? - V.L. van den Berg (South African Family Practice)
The intake of added dietary sugars has escalated dramatically since the 1970s, mostly due to a global increase in the consumption of sugar-sweetened beverages (SSBs). This trend has sparked concerns among scientists and consumers alike regarding the safety of added dietary sugars. The popular media often accuse dietary sugars of being detrimental to health. However, when consumed in moderate amounts, current research does not support the premise that added dietary sugar has a detrimental effect on dental health, mental health and behaviour, weight management, chronic diseases of lifestyle, or the intake of micronutrients. However, SSBs represent concentrated and energy-dense forms of dietary sugars, easily consumed in large amounts. Not surprisingly, excessive consumption of these beverages is associated with weight gain and obesity. Intake of more than one to two drinks per day is also linked to the metabolic syndrome (MS), insulin resistance, type 2 diabetes, cardiovascular diseases, hypertension, gout and non-alcoholic fatty liver disease. Experimental studies suggest that excessive fructose intake may play a direct role in the metabolic changes that manifest as the MS, but further research into this is required. Current recommendations state that added sugars may be enjoyed in moderation as part of a balanced diet, with an appropriate energy intake to achieve or maintain healthy weight. However, excessive intake of added sugars, particularly fructose-containing sugars, should be avoided, and the energy intake from SSBs should be limited to less than 400-600 kJ per day.